Models of Saturn's Equatorial Ionosphere Based on In Situ Data From Cassini's Grand Finale. Issue 18 (27th September 2018) - Moore, L.; Cravens, T. E.; Müller‐Wodarg, I.; Perry, M. E.; Waite, J. H.; Perryman, R.; Nagy, A.; Mitchell, D.; Persoon, A.; Wahlund, J.‐E.; Morooka, M. W.
Abstract: We present new models of Saturn's equatorial ionosphere based on the first in situ measurements of its upper atmosphere. The neutral spectrum measured by Cassini's Ion and Neutral Mass Spectrometer, which includes substantial methane, ammonia, and organics in addition to the anticipated molecular hydrogen, helium, and water, serves as input for unexpectedly complex ionospheric chemistry. Heavy molecular ions are found to dominate Saturn's equatorial low‐altitude ionosphere, with a mean ion mass of 11 Da. Key molecular ions include H3 O + and HCO + ; other abundant heavy ions depend upon the makeup of the mass 28 neutral species, which cannot be uniquely determined. Ion and Neutral Mass Spectrometer neutral species lead to generally good agreement between modeled and observed plasma densities, though poor reproduction of measured H + and H3 + variability and an overabundance of modeled H3 + potentially hint at missing physical processes in the model, including a loss process that affects H3 + but not H + . Plain Language Summary: Cassini's Grand Finale enabled the first‐ever direct measurements of Saturn's upper atmosphere. Here we use Cassini's unique measurements to construct new models of the plasma in this important boundary region that separates the dense lower atmosphere from space. Based on the complex array of observed gases, we find that heavy molecular ions are dominant near Saturn's equator. This surprising result demonstrates that the chemistry in Saturn's equatorial upper atmosphere is substantially more complex than anticipated. The presence of these unexpected ions potentially represents a new method of monitoring Saturn's ionosphere remotely. Furthermore, as other Cassini measurements indicate that the complex chemistry is likely driven by an influx of ring‐derived material, such observations may even help to track the evolution of Saturn's rings as they lose mass to its atmosphere. Key Points: Unexpectedly complex influx of ring material is found in Saturn's equatorial upper atmosphere, including organics, water, and nanograins Ring influx leads to reduction in major ions (H + and H3 + ); heavier molecular ions dominate Saturn's low‐altitude equatorial ionosphere Major molecular ions at low‐altitude are still uncertain but are likely to include H3 O + and HCO +, and the mean modeled ion mass is 11 Da